Omnibus Law in Indonesia: Legal Protection of Workers in Employment Contracts - Muhammad Rizky Ramadhan; Muhammad Kamal; Mochammad Andry Wardhana Wikra Mamonto (Golden Ratio of Law and Social Policy Review (GRLSPR), 2021)
This research finds out and analyze the regulation regarding legal protection for workers in work agreements and to find out and analyze the implications of the existence of the work copyright law on the legal protection of workers. This research uses normative research methods. The results of this study indicate that the synchronization of legal protection arrangements for workers in the agreement where the Legal Protection of Workers is regulated in the Manpower Act, in its continuity to workers is as a guide in providing legal protection for workers, namely in terms of providing legal certainty, justice, and benefits. for workers. The legal rules contained in this UUK have provided very clear instructions or guidelines, both for employers and workers, but in practice they are still far from what has been stipulated in the UUK. The government's efforts in providing legal protection to workers through the making of laws and regulations have been quite good. But so far, the government's efforts in providing legal protection to workers can be said to be minimal. In order for this to run as desired, the authors suggest that the Government should pay attention to the rights and welfare of workers, including in terms of legal protection for workers. The contents of the Civil Code, the Manpower Law and the Employment Copyright Law related to the legal protection of labor must be affirmed and realized as appropriate and workers must carry out their obligations in order to obtain legal rights and protection. points that are generally considered burdensome for workers in obtaining welfare